The impact of private-sector provision on equitable utilisation of coronary revascularisation in London. Issue 8 (10th August 2007) - Mindell, J; Klodawski, E; Fitzpatrick, J; Malhotra, N; McKee, M; Sanderson, C
Abstract : Objective: To investigate the impact of including private-sector data on assessments of equity of coronary revascularisation provision using NHS data only. Design: Analyses of hospital episodes statistics and private-sector data by age, sex and primary care trust (PCT) of residence. For each PCT, the share of London's total population and revascularisations (all admissions, NHS-funded, and privately-funded admissions) were calculated. Gini coefficients were derived to provide an index of inequality across subpopulations, with parametric bootstrapping to estimate confidence intervals. Setting: London. Participants: London residents undergoing coronary revascularisation April 2001–December 2003. Intervention: Coronary artery bypass graft or angioplasty. Main outcome measures: Directly standardised revascularisation rates, Gini coefficients. Results: NHS-funded age-standardised revascularisation rates varied from 95.2 to 193.9 per 100 000 and privately funded procedures from 7.6 to 57.6. Although the age distribution did not vary by funding, the proportion of revascularisations among women that were privately funded (11.0%) was lower than among men (17.0%). Privately funded rates were highest in PCTs with the lowest death rates (p = 0.053). NHS-funded admission rates were not related to deprivation nor age-standardised deaths rates from coronary heart disease. Privately funded admission rates were lower in more deprived PCTs. NHS provision was significantly more egalitarian (Gini coefficient 0.12) than the private sector (0.35). Including all procedures was significantly less equal (0.13) than NHS-funded care alone. Conclusion: Private provision exacerbates geographical inequalities. Those responsible for commissioning care for defined populations must have access to consistent data on provision of treatment wherever it takes place.